In-sacco digestion of sugar constituents of cell wall of berseem and guinea grass at different stages of maturity - SINGH, MUKHVINDER; GUPTA, B K (The Indian Journal of Animal Sciences, 2013)
Rhamnose, arabinose, xylose, mannose, galactose and glucose in different proportions were present in cell wall before and after in-sacco digestion of berseem leaves, stems and guinea grass at different stages of maturity. Xylose and glucose with lower digestibility are increased while arabinose and galactose with high digestibility decreased. The results confirmed digestibility of berseem. stem decreases with successive regrowtns due to increased proportion of stem. Comparison of CWM of berseem leaves did not vary with successive regrowths. In guinea grass, xylose from xylans was the least digestible sugar at all stages of growth. It is concluded that the concentration of ratio of rapidly arabinose +glucose to slowly xylose+ uronie acid degradable CW sugars in a given forage species, determines the rate of cell wall digestion by rumen microrgainism.